Exchange rate risk and convergence to the Euro - Lucjan T. Orlowski (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2004)
This paper proposes a new monetary policy framework for effectively navigating the path to adopting the euro. The proposed policy is based on relative inflation forecast targeting and incorporates an ancillary target of declining exchange rate risk, which is suggested as a key criterion for evaluating the currency stability. A model linking exchange rate volatility to differentials over the euro zone in both inflation (target variable) and interest rate (instrument variable) is proposed. The model is empirically tested for the Czech Republic, Poland and Hungary, the selected new Member States of the EU that use direct inflation targeting to guide their monetary policies. The empirical methodology is based on the TARCH(p,q,r)-M model.
Keywords: E42; E52; F36; P24; 330; exchange rate risk; inflation targeting; monetary convergence; euro area; new EU Member States